Making reform happen : the state and economic development in South Korea, Cambodia, Laos and Vietnam - Seung-Ho Kwon (Cambridge Scholars Publishing, 2019)
This book provides readers with a holistic picture of government reform activity in four countries--namely, South Korea, Cambodia, Laos and Vietnam--located in East and Southeast Asia. The case study of each country offers a detailed understanding of their respective reform trajectories and the context within which actions have been taken.